Optimizing The Potential of Waqf Management in Indonesia Using A Blockchain Technology Approach - Fitri Khairunisah, Ikhsanti (Green Publisher Indonesia, 2025)
The presence of innovation in the world of digital finance in recent years has attracted attention from various parties. This digital financial innovation is commonly known as financial technology. The potential of waqf is large in Indonesia and increases every year but is not offset by a high level of realization as well. This research aims to analyze the optimization of waqf management with blockchain technology in Indonesia. The results showed that in Indonesia it is quite possible to implement blockchain waqf, with a very majority MSULIM population, a flexible waqf concept, and an increasing trend in the halal industry. Blockchain technology can also increase transparency, security, efficiency and effectiveness in waqf management in Indonesia.